2014
DOI: 10.1038/ncomms6068
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins

Abstract: Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(170 citation statements)
references
References 72 publications
(101 reference statements)
6
159
0
5
Order By: Relevance
“…Interestingly, a recent meta-analysis study found that genetic variances in the SORT1 locus are associated with the LDL-cholesterol response to statin therapy. 42 Our study demonstrates that regulation of the LDLR by the (P)RR is a post-transcriptional event culminating in lysosomal degradation of the LDLR. Grossly, 2 cellular scenarios may fit this pattern of regulation.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, a recent meta-analysis study found that genetic variances in the SORT1 locus are associated with the LDL-cholesterol response to statin therapy. 42 Our study demonstrates that regulation of the LDLR by the (P)RR is a post-transcriptional event culminating in lysosomal degradation of the LDLR. Grossly, 2 cellular scenarios may fit this pattern of regulation.…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta-analysis using individual subject data collected from 32,258 patients treated with atorvastatin 10-80 mg, rosuvastatin 5-40 mg, or simvastatin 10-80 mg showed that the standard deviation of LDL-C reduction for all statins and doses ranged from 13 to 18%, whereas the percentage of patients experiencing a suboptimal response (\30% reduction in LDL-C) ranged from 5 to 53% [15]. This somewhat unpredictable response to statins is thought to be due to a complex interplay between genetic and environmental factors [16,17] that translates into a large variability in the balance between cholesterol synthesis and absorption and, at least in part, a compensatory increase in intestinal cholesterol uptake [18,19]. Recently, the PRECISE-IVUS (Plaque Regression With Cholesterol Absorption Inhibitor or Synthesis Inhibitor Evaluated by Intravascular Ultrasound) trial found that sterols (lathosterol, campesterol, and sitosterol) and their ratio to cholesterol increased with atorvastatin monotherapy but decreased with the atorvastatin-ezetimibe combination.…”
Section: Variability In Individual Response To Statin Therapymentioning
confidence: 99%
“…8 There is some debate as to whether statins are as effective at primary prevention of CVD events in women as they are in men, [9][10][11] so further investigation of potential sex differences in statin response is warranted. A number of pharmacogenetic studies have sought to identify singlenucleotide polymorphisms (SNPs) that influence LDL-C statin response using candidate-gene and genome-wide association approaches, but the findings to date account for less than 10% of the variation in statin-induced LDL-C lowering variability, [12][13][14][15][16][17][18][19][20] with variants near the apolipoprotein E (APOE) and lipoprotein, Lp(a) (LPA) genes showing some of the strongest and most replicated signals. 17,18,20 Genetic association studies of TG statin response have been even less fruitful, with two published genome-wide association studies revealing no genome-wide significant hits 15,16 and only a modest number of significant associations reported with genetic variation in candidate genes, such as lipoprotein lipase (LPL), 21 cholesteryl ester transfer protein, plasma (CETP), ATP-binding cassette, sub-family B (MDR/TAP), member 1 (ABCB1) 22 and APOE.…”
Section: Introductionmentioning
confidence: 99%